APPLICATION ELECTRONIC MONITORING SYSTEM A COMPARATIVE STUDY BETWEEN JORDANIAN AND FRENCH LEGISLATION" (Lex localis - Journal of Local Self-Government, 2025)
The electronic monitoring  system is one of the most prominent developments in the criminal legal system in the Hashemite Kingdom of Jordan, It was introduced as part of the digital transformation program in the criminal judicial sector,   repeated article (25) of the Jordanian Penal Code and  repeated  Article (114) of the Code of Criminal Procedure granted the criminal judge the authority to implement it. It was first adopted as a measure to enhance the implementation of certain judicial oversight obligations, and then as an alternative to the penalties  affecting  freedom, this was done to encourage the judiciary to implement this type of punishment and avoid short-term custodial sentences, this is in keeping with the modern penal policy that relies on alternative punishments for minor crimes.